Purification and Characterization of NDH-2 Protein and Elucidating Its Role in Extracellular Electron Transport and Bioelectrogenic Activity - Vamshi Krishna, K.; Venkata Mohan, S. (Frontiers in Microbiology, 2019)
In microbial electrochemical systems, transport of electrons from bacteria to an electrode is the key to its functioning. However, the role of several electron transport proteins, especially the membrane bound dehydrogenases which link cellular metabolism to EET pathway is yet to be identified. NDH-2 is a non-proton pumping NADH dehydrogenase located in the inner membrane of several bacteria like Bacillus subtilis, Escherichia coli etc. Unlike NADH dehydrogenase I, NDH-2 is not impeded by a high proton motive force thus helping in increase of metabolic flux and carbon utilization. Herein, NADH dehydrogenase II protein (NDH-2) was heterologously expressed from Bacillus subtilis into Escherichia coli BL21 (DE3) to enhance electron flux through EET pathway and understand its role in current production. We found that E. coli expressing NDH-2 has increased the electron flux through EET and has showed 3 fold increase in current (1.9 µA) production when compared to parent strain (0.4 µA). Furthermore, expression of NDH-2 also resulted in increased biofilm formation which can be corroborated with the decrease in charge transfer resistance of NDH-2 strain and increased NADH oxidation. It was also found that NDH-2 strain can reduce metal oxides (Iron citrate) at a higher rate than uninduced strain suggesting increased electron flux thorough electron transport chain due to NADH dehydrogenase II activity. Purified Ndh2 was found to be 42 kDa and has FAD as cofactor. This work demonstrates that the primary dehydrogenases like NADH dehydrogenases can be reengineered to increase the electron flux in EET pathways which can further enhance the microbial fuel cells performance.